A Comparison of Amphibian and Reptile Diversity Between Disturbed and Undisturbed Environments of Salvatierra, Guanajuato, Mexico. (February 2019) - Leyte-Manrique, Adrian; Abel Antonio, Buelna-Chontal; Miguel Alejandro, Torres-Díaz; Berriozabal-Islas, Christian; Maciel-Mata, Carlos Alberto
Amphibians and reptiles are two groups of vertebrates that are sensitive to changes in their environment. These changes are mostly caused by human activities, which affect the abundance, composition, and distribution of these vertebrates. In this study, we compare the richness and taxonomic diversity of herpetofauna between undisturbed environments (tropical deciduous forest = TDF) and disturbed environments (corn fields = CF) near the towns of Urireo (URI) and San Nicolas de los Agustinos (SNA) in Salvatierra, Guanajuato. We recorded a total of 19 species in the two locations (4 amphibian and 15 reptile species). At the URI locality, 12 species were recorded in CF and 10 in TDF. At the SNA locality, eight species were recorded in CF and seven species in TDF. In addition, we found that overall taxonomic distinctness was greater at URI than SNA across both types of vegetation, with the highest diversity found in TDF of URI. Seven of the 19 species recorded are current allocated to some protection category of NOM-059-SEMARNAT-2010: Lithobates neovolcanicus, Kinosternon integrum, Sceloporus grammicus, Lampropeltis polyzona, Masticophis mentovarius, Salvadora bairdi, and Thamnophis melanogaster differing from other mechanisms such as the International Union for Conservation of Nature and Environmental Vulnerability Score. Our results suggest that carrying out long-term studies that include diversity and taxonomic distinctness in environments with different levels of disturbance, in addition to including characteristics of natural history, might enhance the development of more efficient conservation strategies for these vertebrates.